Local Infiltration Analgesia with Ropivacaine Improves Postoperative Pain Control in Ankle Fracture Patients: A Retrospective Cohort Study - Bao-Liang Li; Xizhe Liu; Lihua Cui; Wenqian Zhang; Hui Pang; Mingshan Wang; Hai-Qiang Wang (Pain Research and Management)
Purpose. The study aimed at investigating the effect of local infiltration analgesia (LIA) with ropivacaine on postoperative analgesia for patients undergoing ankle fracture surgery. Methods. Consecutive patients were retrospectively included and analysed according to their medical records from July 2014 to August 2018 in a tertiary hospital. Inclusion criteria were patients undergoing open reduction and internal fixation (ORIF) for ankle fractures under general anaesthesia. Moreover, patients should have received intravenous patient-controlled analgesia (iPCA) or LIA + iPCA for postoperative pain relief. The primary outcome indicator was visual analogue scale (VAS) from 8 hours to 48 hours after surgery. Secondary outcomes included postoperative opioid requirement, need for rescue medication, opioid-related adverse effects, and wound complications. Results. In total, 89 consecutive patients were included in the study. There were 48 males and 41 females. The average age was 44.6 ± 7.0 years, and VAS scores were significantly lower in the LIA + iPCA group at 8 hours after surgery (1.51 ± 0.58 cm vs 4.77 ± 1.83 cm, p<0.001). The time to first tramadol consumption was longer (580 ± 60.9 minutes vs 281 ± 86.4 minutes, p<0.001), and the number of patients who need tramadol was lower in the LIA + iPCA group (18 vs 26, p=0.04). There was a statistically significant reduction in morphine consumption (25.1 ± 6.3 mg vs 73.4 ± 8.2 mg, p<0.001) and opioid-related side effects in the LIA + iPCA group (4 vs 10, p=0.023). No major wound complications were noted in either group. However, there were 2 cases with superficial wound necrosis in group LIA + iPCA and 3 patients with superficial wound necrosis in group iPCA, and all cured by local wound care. Conclusions. The retrospective cohort study indicates that LIA with ropivacaine can provide better early postoperative pain management with a reduction of VAS scores for ankle fracture surgery. Patients receiving wound infiltration also experience decreased opioid consumption, a lower rate of analgesia-related side effects, and comparable wound complication rate.